Sikap Dan Motivasi Ibu Terhadap Pelaksanaan Imunisasi Campak Dalam Pencegahan Campak - Bambang Mardisentosa; Astrinda Ayu Bidara (Jurnal Kesehatan, 2020)
ABSTRACT Measles is a disease that is easily infected, Ministry of Health noted the number of cases of measles in Indonesia is very much and tends to increase in the last five years. Research Purposes To determine the level of knowledge of attitudes and motivation of mothers against measles immunization in the prevention of measles simultaneously. Research method in this study uses a comparative causal or cross sectional approach using multicollinearity normality test, heteroscedasticity, linearity, multiple regression, t test, and f test. The population is 58 respondents. The sampling technique in this study uses purposive sampling. The instrument used in the form of questionnaire sheets. The technical analysis above uses Univariate and Bivariate analysis. Research Results Based on t-test, the level of Knowledge and Motivation did not significantly influence the measles immunization in the prevention of measles, the attitude variable had a significant effect on measles immunization in the prevention of Measles. Based on the results of the F test study (Simultaneous shows that the independent variable knowledge level of Attitude and Motivation of Mothers against Measles Immunization in Measles Prevention the results of Table 7.515 with a value of Sig. 0.000. Conclusions and Recommendations The results of the study have the effect of the level of knowledge of attitudes and maternal motivation on measles immunization in the prevention of measles.